Modified carbon-based carbon dioxide adsorption material and preparation method thereof

The treatment of carbon-based adsorption materials through ozone oxidation modification has improved its surface polarity, and the problem of poor CO2 adsorption effect in the existing technology has been solved, and efficient and environmentally friendly CO2 capture effect has been achieved, providing good results for large-scale applications. potential.

CN119175072APending Publication Date: 2024-12-24CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310746018.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing carbon dioxide adsorption materials have poor CO2 adsorption effect, which is difficult to meet the needs of large-scale CO2 capture technology, and there are problems of high energy consumption and pollution.

Method used

The carbon-based adsorption material is treated with ozone oxidation modification to improve its surface polarity, thereby enhancing the adsorption effect on CO2. The method is simple to operate and does not cause hazardous waste.

Benefits of technology

It significantly improves the CO2 adsorption effect, is suitable for large-scale CO2 capture processes, the surface polarity of the material is enhanced, the CO2 adsorption amount increases, and the process is safe and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119175072A_ABST
    Figure CN119175072A_ABST
Patent Text Reader

Abstract

The invention relates to a modified carbon-based carbon dioxide adsorption material and a preparation method thereof.The preparation method comprises the steps that ozone makes contact with the carbon-based adsorption material for modification treatment, the surface polarity of the carbon-based adsorption material is improved, and then the CO2 adsorption effect is improved. The method is simple to operate, does not generate any hazardous waste, and has good application potential in a large-scale CO2 trapping process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a carbon dioxide adsorbent material, and in particular, to a modified carbon-based carbon dioxide adsorbent material and a preparation method thereof. Background Art

[0002] Global warming has brought extensive impacts on the survival, development and stability of human society, and is one of the most severe and complex challenges facing mankind in the 21st century. It is reported that about 60% of the greenhouse effect is caused by carbon dioxide gas. As one of the main greenhouse gases, its emission reduction has become a global issue. At present, the adsorption method of CO2 capture technology has low energy consumption and low pollution, and is a good carbon emission reduction technology. However, the existing adsorption materials have an unsatisfactory effect on CO2 adsorption, which makes it difficult to meet the large-scale promotion of this technology. Summary of the invention

[0003] The purpose of the present disclosure is to provide a modified carbon-based carbon dioxide adsorption material and a preparation method thereof, which is simple to operate, does not produce any hazardous waste, and has good application potential in large-scale CO2 capture processes.

[0004] A first aspect of the present disclosure provides a method for preparing a modified carbon-based carbon dioxide adsorbent material, the method comprising contacting ozone with the carbon-based adsorbent material for modification.

[0005] Optionally, the conditions for the modification treatment include: relative to 1 kg of the carbon-based adsorbent material, the flow rate of the introduced ozone is 0.01-5 L / min, the pressure is 1-5 bar, and the introduction time is 0.1-24 h; the temperature of the modification treatment is 25-100° C., and the time is 0.1-24 h.

[0006] Optionally, the amount of ozone used is 0.15 to 72 L, preferably 0.5 to 72 L, relative to 1 kg of the carbon-based adsorption material.

[0007] Optionally, the raw material of the carbon-based adsorption material is activated carbon, and the activated carbon includes one or more of wood activated carbon, coconut shell activated carbon and coal activated carbon.

[0008] Optionally, the specific surface area of ​​the carbon-based adsorption material is 500 to 3000 m 2 / g, the porosity is 60-90%, and the average pore size is 2-10nm.

[0009] Optionally, the shape of the carbon-based adsorption material includes one or more of powder, granular and honeycomb shapes; preferably, the shape of the carbon-based adsorption material is honeycomb, and the honeycomb shape includes one or more of honeycomb rectangular blocks, honeycomb circular blocks and honeycomb hexagonal blocks; more preferably, equidistant honeycomb holes are provided on the cross-section of the honeycomb rectangular blocks, honeycomb circular blocks and honeycomb hexagonal blocks, and the honeycomb holes are arranged along the axial through holes or blind holes of the honeycomb rectangular blocks, honeycomb circular blocks and honeycomb hexagonal blocks.

[0010] Optionally, the side length of the rectangular honeycomb block, the diameter of the circular honeycomb block and the side length of the hexagonal honeycomb block are each independently 30 to 150 mm; the cross-section of the honeycomb hole is circular or square, and the size range of the honeycomb hole is 1 to 10 mm.

[0011] The second aspect of the present disclosure provides a modified carbon-based carbon dioxide adsorption material prepared by the preparation method described in the first aspect of the present disclosure.

[0012] Optionally, the modified carbon-based carbon dioxide adsorbent material and the carbon-based adsorbent material are at 1500-1800 cm -1 The intensity ratio of the infrared absorption peak at 700-1200 cm -1 The intensity ratio of the infrared absorption peaks at is 2-15, preferably 2-10.

[0013] Optionally, the specific surface area of ​​the modified carbon-based carbon dioxide adsorbent material is 300 to 3000 m 2 / g, and a porosity of 60-90%; preferably, based on the specific surface area of ​​the carbon-based adsorbent material, the specific surface area of ​​the modified carbon-based carbon dioxide adsorbent material is 70-100 area %.

[0014] Through the above technical solution, the present disclosure provides a modified carbon-based carbon dioxide adsorbent material and a preparation method thereof, which uses ozone to oxidatively modify the carbon-based adsorbent material, thereby increasing the surface polarity of the carbon-based adsorbent material and thereby increasing the adsorption effect on CO2. The method disclosed in the present disclosure is simple to operate, does not generate any hazardous waste, and has good application potential in large-scale CO2 capture processes.

[0015] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0017] Figure 1 is an infrared absorption graph of the modified carbon-based carbon dioxide adsorbent material and the carbon-based adsorbent material prepared in Examples 1 to 2 of the present disclosure;

[0018] Figure 2 This is a graph of the CO2 adsorption amount of the modified carbon-based carbon dioxide adsorbent material and the carbon-based adsorbent material prepared in Examples 1 to 2 of the present disclosure. DETAILED DESCRIPTION

[0019] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0020] A first aspect of the present disclosure provides a method for preparing a modified carbon-based carbon dioxide adsorbent material, the method comprising contacting ozone with the carbon-based adsorbent material for modification.

[0021] The present invention uses ozone to oxidatively modify the carbon-based adsorbent material to increase the surface polarity of the carbon-based adsorbent material, thereby improving the adsorption effect of CO2. The method is simple to operate, does not produce any hazardous waste, and has good application potential in large-scale CO2 capture processes.

[0022] In one embodiment of the present disclosure, the conditions of the modification treatment include: relative to 1 kg of the carbon-based adsorbent material, the flow rate of the introduced ozone is 0.01-5 L / min, the pressure is 1-5 bar, and the introduction time is 0.1-24 h; the temperature of the modification treatment is 25-100 ° C, and the time is 0.1-24 h. In one embodiment, the modification treatment can be: placing the carbon-based adsorbent material in a closed environment, first introducing ozone for a period of time, and then turning off the ozone to carry out the modification treatment. In a preferred embodiment, the time of the modification treatment is the same as the time of introducing ozone. In the above embodiment, by selecting ozone with a preferred flow rate and pressure, ozone can be fully reacted with the carbon-based adsorbent material, thereby oxidatively modifying the surface of the carbon-based adsorbent material to improve the adsorption effect of carbon dioxide.

[0023] In one embodiment of the present disclosure, the amount of ozone used is 0.15 to 72 L, preferably 0.5 to 72 L, relative to 1 kg of the carbon-based adsorbent material. In the above embodiment, by selecting the preferred amount of ozone, the oxygen-containing functional groups on the surface of the carbon-based adsorbent material can be further increased, thereby improving its oxidation effect and facilitating the adsorption of carbon dioxide.

[0024] In one embodiment of the present disclosure, the raw material of the carbon-based adsorption material is activated carbon, and the activated carbon includes one or more of wood activated carbon, coconut shell activated carbon and coal activated carbon. In one embodiment, the method of making activated carbon into carbon-based adsorption material may include extrusion molding and briquetting molding. In the above embodiment, the activated carbon with rich pore structure and large specific surface area is selected as the raw material of the carbon-based adsorption material, which is conducive to the modification treatment thereof with ozone, and the activated carbon is widely available and low in cost, and is suitable for industrial large-scale production.

[0025] In one embodiment of the present disclosure, the specific surface area of ​​the carbon-based adsorbent material is 500 to 3000 m 2 / g, porosity of 60-90%, and average pore size of 2-10nm. In the above embodiment, by preferably selecting a carbon-based adsorbent material with a large specific surface area and high porosity, it is beneficial to fully contact and react with ozone.

[0026] In one embodiment of the present disclosure, the shape of the carbon-based adsorbent material includes one or more of powder, granular and honeycomb; in a preferred embodiment, the shape of the carbon-based adsorbent material is honeycomb, and the honeycomb includes one or more of honeycomb rectangular blocks, honeycomb circular blocks and honeycomb hexagonal blocks; further preferably, the honeycomb rectangular blocks, honeycomb circular blocks and honeycomb hexagonal blocks are provided with equidistant honeycomb holes on their cross-sections, and the honeycomb holes are provided along the axial through holes or blind holes of the honeycomb rectangular blocks, honeycomb circular blocks and honeycomb hexagonal blocks. In the above embodiment, by selecting the preferred honeycomb carbon-based adsorbent material, the specific surface area of ​​the carbon-based adsorbent material can be further increased, which is beneficial to the modification treatment of ozone.

[0027] In one embodiment of the present disclosure, the side length of the honeycomb rectangular block, the diameter of the honeycomb circular block and the side length of the honeycomb hexagonal block are each independently 30 to 150 mm; the cross-section of the honeycomb hole is circular or square, and the size range of the honeycomb hole is 1 to 10 mm, preferably 3 to 10 mm. In the above embodiment, "the size of the honeycomb hole" refers to the diameter or side length of the honeycomb hole. In the above embodiment, the honeycomb carbon-based adsorption material has a rich pore structure, which further improves the effect of the ozone modification treatment.

[0028] The second aspect of the present disclosure provides a modified carbon-based carbon dioxide adsorption material prepared by the preparation method described in the first aspect of the present disclosure.

[0029] In one embodiment of the present disclosure, the modified carbon-based carbon dioxide adsorbent material and the carbon-based adsorbent material are at 1500-1800 cm -1The intensity ratio of the infrared absorption peak at 700-1200 cm -1 The intensity ratio of the infrared absorption peak at 1500-1800 cm -1 700~1200cm -1 The infrared absorption at the site is significantly enhanced, indicating that its oxygen-containing functional groups have increased, which is conducive to the adsorption of carbon dioxide.

[0030] In one embodiment of the present disclosure, the specific surface area of ​​the modified carbon-based carbon dioxide adsorbent material is 300 to 3000 m 2 / g, and a porosity of 60-90%; in a preferred embodiment, based on the specific surface area of ​​the carbon-based adsorbent material, the specific surface area of ​​the modified carbon-based carbon dioxide adsorbent material is 70-100% by area. In the above embodiment, the specific surface area of ​​the modified carbon-based carbon dioxide adsorbent material decreases, but the oxygen-containing functional groups on its surface increase significantly, which is conducive to the adsorption of carbon dioxide; wherein the specific surface area loss of the modified carbon-based carbon dioxide adsorbent material does not exceed 30%.

[0031] Through the above technical solution, the present disclosure provides a modified carbon-based carbon dioxide adsorbent material and a preparation method thereof, which uses ozone to oxidatively modify the carbon-based adsorbent material, thereby increasing the surface polarity of the carbon-based adsorbent material and thereby increasing the adsorption effect on CO2. The method is simple to operate, does not generate any hazardous waste, and has good application potential in large-scale CO2 capture processes.

[0032] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.

[0033] In the following examples, unless otherwise specified, the raw materials used are commercially available products.

[0034] The materials obtained in the examples and comparative examples were subjected to infrared analysis using a Fourier transform infrared spectrometer. The infrared testing method was as follows: the Fourier transform infrared spectrometer (FTIR) was an AVATAR360 model from NICOLET, USA. The solid sample was mixed with dry KBr and ground, then pressed into a tablet for testing. The transmission mode was usually selected, and the scanning range was 4000-400 cm -1 .

[0035] Example 1

[0036] 1) Extruding wood activated carbon to form a porous honeycomb circular block carbon-based adsorption material A with a specific surface area of ​​2000m 2 / g, porosity of 88%, average pore size of 3nm, CO2 adsorption of 2.0%; the honeycomb circular block carbon-based adsorption material is provided with equidistant circular honeycomb holes, and the honeycomb holes are arranged along the axial through holes of the honeycomb circular block, wherein the diameter of the honeycomb circular block is 100mm, and the diameter of the honeycomb hole is 4mm;

[0037] 2) 500g of honeycomb circular block carbon-based adsorbent material is regularly installed on a porous support plate in an oxidation bed, and 36L of ozone is introduced for modification treatment (i.e., relative to 1kg of carbon-based adsorbent material, the amount of ozone used is 72L), the flow rate of the introduced ozone is adjusted to 0.1L / min (i.e., relative to 1kg of carbon-based adsorbent material, the flow rate of the introduced ozone is 0.2L / min), the pressure is 1 bar, the time of introducing ozone is 6h, the temperature of the modification treatment is 25°C, and the time is 6h; after the modification treatment is completed, the introduction of ozone is stopped to obtain a modified carbon-based carbon dioxide adsorbent 1; wherein the structure of the modified carbon-based carbon dioxide adsorbent 1 is shown in Table 1 and Figures 1-2 As shown;

[0038] from Figure 1 It can be seen that the carbon-based adsorbent material A before modification is between 1500 and 1800 cm -1 700~1200cm -1 The intensity of the infrared absorption peaks at 1500-1800 cm -1 There is almost no infrared absorption peak of -C=O bond at 700~1200cm -1 There is a weak -OH infrared absorption peak at 1500-1800cm -1 There is a broad -C=O bond infrared absorption peak at 700-1200cm -1 There is a high and sharp -OH infrared absorption peak at the surface, indicating that the -C=O bond and -OH bond content of the modified carbon-based carbon dioxide adsorbent material 1 prepared in Example 1 are significantly increased, which greatly increases the polarity of the material;

[0039] from Figure 2 It can be seen that compared with the carbon-based adsorbent material, the CO2 adsorption amount of the modified carbon-based carbon dioxide adsorbent material 1 is significantly increased, indicating that the CO2 adsorption effect is improved.

[0040] Example 2

[0041] The method of Example 1 was adopted, except that: 24 L of ozone was introduced for modification (i.e., the amount of ozone was 48 L relative to 1 kg of carbon-based adsorbent material), the flow rate of ozone was adjusted to 0.1 L / min (i.e., the flow rate of ozone introduced was 0.2 L / min relative to 1 kg of carbon-based adsorbent material), and the introduction time was 4 h to obtain a modified carbon-based carbon dioxide adsorbent material 2; wherein the structure of the modified carbon-based carbon dioxide adsorbent material 2 is shown in Tables 1 and Figures 1-2 As shown;

[0042] from Figure 1 It can be seen that the modified carbon-based carbon dioxide adsorbent material 2 modified in Example 2 has a surface area of ​​1500-1800 cm -1 There is a -C=O bond infrared absorption peak at 700-1200cm -1 There is an -OH infrared absorption peak at , indicating that the content of -C=O bonds and -OH bonds on the surface of the modified carbon-based carbon dioxide adsorbent material 2 prepared in Example 2 increases, which increases the polarity of the material.

[0043] Example 3

[0044] The method of Example 1 is adopted, with the only difference being that 80 L of ozone is introduced for modification (i.e., the amount of ozone used is 160 L relative to 1 kg of carbon-based adsorbent material), the flow rate of the ozone is adjusted to 8 L / min (i.e., the flow rate of the ozone introduced is 16 L / min relative to 1 kg of carbon-based adsorbent material), and the introduction time is 10 min to obtain modified carbon-based carbon dioxide adsorbent material 3.

[0045] Example 4

[0046] The method of Example 1 is adopted, with the only difference being that: 0.05 L of ozone is introduced for modification (i.e., the amount of ozone used is 0.1 L relative to 1 kg of carbon-based adsorption material), the flow rate of the ozone is adjusted to 0.01 L / min (i.e., the flow rate of the ozone introduced is 0.02 L / min relative to 1 kg of carbon-based adsorption material), and the introduction time is 5 min, to obtain modified carbon-based carbon dioxide adsorption material 4.

[0047] Example 5

[0048] The method of Example 1 is adopted, except that: the specific surface area of ​​2000m 2 / g of carbon-based adsorbent material A was replaced with a specific surface area of ​​400m 2 / g of carbon-based adsorbent material B, the porosity of carbon-based adsorbent material B is 40%, the average pore size is 15nm, and the CO2 adsorption capacity is 1.9%, thereby obtaining modified carbon-based carbon dioxide adsorbent material 5.

[0049] Comparative Example 1

[0050] The method of Example 1 was adopted, except that ozone was replaced with the same amount of oxygen (with a purity of 100%) for modification treatment to obtain comparative material 1.

[0051] Comparative Example 2

[0052] The method of Example 1 was adopted, except that ozone was replaced with the same amount of air for modification treatment to obtain comparative material 2.

[0053] Test Case

[0054] The modified materials (i.e., modified carbon-based carbon dioxide adsorbent materials 1-5 prepared in Examples 1-5 and comparative materials 1-2 prepared in Comparative Examples 1-2) were tested for their adsorption effect on carbon dioxide. The test method was as follows: CO2 adsorption was performed in a fixed bed reactor. Before adsorption, the modified material was first desorbed at 120°C, and then a mixed gas of CO2 / N2 was introduced for adsorption. The adsorption conditions were as follows: in a simulated flue gas atmosphere (the volume content of CO2 was 15%, the volume content of N2 was 85%, and the temperature was 40°C), a thermogravimetric analyzer was used to measure the CO2 adsorption amount of the modified material, wherein the CO2 adsorption amount of the modified material = 100% × (the weight of the modified material after CO2 adsorption - the net weight of the modified material) / the net weight of the modified material; the measured results were as follows:

[0055]

[0056] By comparing Example 1 with Examples 3 to 4, it can be seen that when Example 1 adopts the preferred embodiment of the present disclosure, the flow rate of ozone is 0.01 to 5 L / min relative to 1 kg of the carbon-based adsorbent material, and the amount of ozone is 0.15 to 72 L relative to 1 kg of the carbon-based adsorbent material, the modification effect of the carbon-based adsorbent material is better, and the CO2 adsorption capacity of the modified material is higher; By comparing Example 1 with Example 5, it can be seen that Example 1 adopts the preferred carbon-based adsorbent material of the present disclosure with a specific surface area of ​​500 to 3000 m 2 / g, the porosity is 60-90%, and the average pore size is 2-10nm, the modification effect of the carbon-based adsorption material is better, and the CO2 adsorption capacity of the modified material is higher.

[0057] Comparison of Comparative Examples 1 to 2 with Examples 1 to 5 shows that when Comparative Examples 1 to 2 do not use the method disclosed in the present invention, the modification effect of the carbon-based adsorbent material is poor, and the CO2 adsorption capacity of the modified material is low. However, Examples 1 to 5 use the method disclosed in the present invention to effectively increase the oxygen-containing functional groups of the carbon-based adsorbent material, thereby increasing the CO2 adsorption capacity and improving the CO2 adsorption efficiency.

[0058] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0059] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0060] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing a modified carbon-based carbon dioxide adsorbent material, characterized in that: The preparation method comprises bringing ozone into contact with a carbon-based adsorption material for modification treatment.

2. The preparation method according to claim 1, characterized in that: The conditions for the modification treatment include: relative to 1 kg of the carbon-based adsorption material, the flow rate of the introduced ozone is 0.01-5 L / min, the pressure is 1-5 bar, and the introduction time is 0.1-24 h; the temperature of the modification treatment is 25-100° C., and the time is 0.1-24 h.

3. The preparation method according to claim 1, characterized in that: The amount of ozone used is 0.15 to 72 L, preferably 0.5 to 72 L, relative to 1 kg of the carbon-based adsorption material.

4. The preparation method according to claim 1, characterized in that: The raw material of the carbon-based adsorption material is activated carbon, and the activated carbon includes one or more of wood activated carbon, coconut shell activated carbon and coal-based activated carbon.

5. The preparation method according to claim 1, characterized in that: The specific surface area of ​​the carbon-based adsorption material is 500 to 3000 m 2 / g, the porosity is 60-90%, and the average pore size is 2-10nm.

6. The preparation method according to claim 1, characterized in that: The shape of the carbon-based adsorption material includes one or more of powder, granular and honeycomb shapes; preferably, the shape of the carbon-based adsorption material is honeycomb, and the honeycomb shape includes one or more of honeycomb rectangular blocks, honeycomb circular blocks and honeycomb hexagonal blocks; more preferably, equidistant honeycomb holes are provided on the cross-section of the honeycomb rectangular blocks, honeycomb circular blocks and honeycomb hexagonal blocks, and the honeycomb holes are arranged along the axial through holes or blind holes of the honeycomb rectangular blocks, honeycomb circular blocks and honeycomb hexagonal blocks.

7. The preparation method according to claim 6, characterized in that: The side length of the rectangular honeycomb block, the diameter of the circular honeycomb block and the side length of the hexagonal honeycomb block are independently 30 to 150 mm; The cross section of the honeycomb holes is circular or square, and the size of the honeycomb holes ranges from 1 to 10 mm.

8. A modified carbon-based carbon dioxide adsorbent material prepared by the preparation method according to any one of claims 1 to 7.

9. The modified carbon-based carbon dioxide adsorbent material according to claim 8, characterized in that: The modified carbon-based carbon dioxide adsorbent material and the carbon-based adsorbent material are at 1500-1800 cm -1 The intensity ratio of the infrared absorption peak at 700-1200 cm -1 The intensity ratio of the infrared absorption peaks at is 2-15, preferably 2-10.

10. The modified carbon-based carbon dioxide adsorbent material according to claim 8, characterized in that: The specific surface area of ​​the modified carbon-based carbon dioxide adsorbent material is 300 to 3000 m 2 / g, and a porosity of 60-90%; preferably, based on the specific surface area of ​​the carbon-based adsorbent material, the specific surface area of ​​the modified carbon-based carbon dioxide adsorbent material is 70-100 area %.

Citation Information

Cited By

  • Preparation method and application of carbon material for carbon dioxide-waste oil double-effect adsorption

    CN119971997A